PENGARUH RASIO KEUANGAN DAN VOLUME PERDAGANGAN TERHADAP RETURN SAHAM - Effendi, Erdianza Septian; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to test the influence of net profit margin, debt to equity ratio, cash ratio, dividend payout ratio, total asset turn over and trade volume to the stock return. Research method used is purposive sampling with the sample of the as many as 163 financial reports of 45 company property and real estate, who go-public at the indonesian stock exchange the period 2011-2014. Testing using a technique regression analysis linear multiple with the tools spss (statistical pagkage for social sciences) version 20, with independent variable for which used is net profit margin, debt to equity ratio, cash ratio, dividend payout ratio, total assets turn over and trade volume and its effect on dependent variable stock return. The result of multiple linear regressions analysis shows that total assets turn over and trade volume influential positive to the stock return. Meanwhile, net profit margin, debt to equity ratio, cash ratio, and dividend payout ratio do not give any influence to the stock return, and the result of R square is 0.15 or 15% of the independent variables give influence to the dependent variable.